USEFUL GAMES AND ACTIVITIES IN TEACHING FOREIGN LANGUAGES - Toshpulatova , Makhbuba Ikromovna (Educational Research in Universal Sciences, 2023)
The article intends to describe how to use mnemonics on learning foreign languages and tries to explain with examples and samples.